The Effects Of Irrigation, Rainfall and Fertilizer Access As Determinants On Waqf Rice Yields and Foundation Economic Independence - Ali Ghiyatsi; Fitria Dwi Larasfeni (International Journal of Management and Business Economics, 2026)
This study examined the effect of irrigation systems, rainfall, and fertilizer access on waqf rice field yields and their implications for the economic independence of the Nuruddin Karangjongkeng Foundation in in Karangjongkeng Village, Brebes Regency, Central Java, Indonesia. The study addressed the low and fluctuating productivity of productive waqf rice fields, which limited their contribution to foundation financing. A quantitative approach with a causal explanatory design was used. The respondents consisted of 22 farmers who cultivated waqf rice fields, selected through total sampling. Data were collected using a five-point Likert scale questionnaire and analyzed through multiple linear regression. The findings showed that the irrigation system had a significant but negative effect on rice field yields, indicating that existing irrigation conditions had not supported productivity effectively. Rainfall had a positive and significant effect and became the most dominant factor affecting yields. Fertilizer access did not have a significant effect on yields, which indicated that fertilizer availability had not yet translated into productive efficiency. Simultaneously, irrigation systems, rainfall, and fertilizer access had a significant effect on rice field yields, with a coefficient of determination of 64.5 percent. The study concluded that climate adaptation, targeted irrigation rehabilitation, and fertilizer efficiency evaluation were needed to improve sustainable yields and strengthen the economic independence of the foundation.